GASTROPOD DIVERSITY AS A BIO-INDICATOR OF AQUATIC POLLUTION IN SIRONJONG GADANG ISLAND PESISIR SELATAN DISTRICT - Sihotang, Usia Xoros; Tanjung, Afrizal; Yoswaty, Dessy (Asian Journal of Aquatic Sciences, 2024)
This study aims to determine the diversity of gastropods and water conditions on Sironjong Gadang Island, Pesisir Selatan Regency. This research was conducted in August 2022 in the waters of Sironjong Gadang Island and the Marine Biology Laboratory and Marine Chemistry Laboratory of the Department of Marine Science, Universitas Riau. The method used in this research is the survey method, which is direct observation of the research area and sampling and measurement of water quality parameters in the field. The results of the study found gastropod species consisting of 4 (four) families, 4 (four) genera, and 8 (eight) species. The diversity value (H') was at a moderate level of diversity. The highest gastropod density was found at Station I, with a density value of 16.33 ind/m², and the lowest density was found at Station III, with a density value of 13.89 ind/m². The highest relative density was Monodonta labia species, with a relative density value of 27.6%, while the lowest relative density was Haustrum-scoring species, with a relative density value of 3.3%. Temperature 28-29˚C; salinity 25-27 ppt; pH 7.91-7.95; brightness 1.55-2.65 m. The sediment type at Station I was dominated by muddy gravel, Station II was dominated by sandy gravel, and Station III was defeated by sandy gravel with a total sediment organic matter content of 6.10-10.05%.